2015
DOI: 10.1371/journal.pone.0122104
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Synovial Molecular Patterns in Patients with Arthritis

Abstract: ObjectivesEarly diagnosis of rheumatoid arthritis (RA) is an unmet medical need in the field of rheumatology. Previously, we performed high-density transcriptomic studies on synovial biopsies from patients with arthritis, and found that synovial gene expression profiles were significantly different according to the underlying disorder. Here, we wanted to further explore the consistency of the gene expression signals in synovial biopsies of patients with arthritis, using low-density platforms.MethodsLow-density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…Datasets with samples of 4 anatomical structures of knee joint, including cartilage, synovial tissues, meniscal tissues, and subchondral bone, can be found in GEO. 17 studies were selected in this study, including 3 studies in knee cartilage, 10 studies in knee synovial tissue, 3 studies in knee meniscal tissue, and 1 study in knee subchondral bone (Table 1) [22][23][24][25][26][27][28][29][30][31]. By integrated analysis, 12945 genes for cartilage, 3238 genes for synovial tissue, 6598 genes for meniscal tissue, and 9570 genes for subchondral bone were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Datasets with samples of 4 anatomical structures of knee joint, including cartilage, synovial tissues, meniscal tissues, and subchondral bone, can be found in GEO. 17 studies were selected in this study, including 3 studies in knee cartilage, 10 studies in knee synovial tissue, 3 studies in knee meniscal tissue, and 1 study in knee subchondral bone (Table 1) [22][23][24][25][26][27][28][29][30][31]. By integrated analysis, 12945 genes for cartilage, 3238 genes for synovial tissue, 6598 genes for meniscal tissue, and 9570 genes for subchondral bone were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Osteoarthritis (OA) is increasingly recognised as a highly heterogeneous group of diseases characterised by variable clinical phenotypes 1,2 . OA heterogeneity underlines the various responses to current therapies for individual patients and inconsistency of outcomes observed in clinical practice 1,2 . There is, therefore, an urgent need to differentiate between distinct clinical phenotypes, especially in the early stages of the disease and progressive phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Using high-density and customized low-density gene expression platforms, we also found heterogeneous expression of T cell (lymphoid)-associated transcripts in RA synovial tissue. In a group of 32 biopsies obtained in treated and untreated patients, we observed that expression of these transcripts displayed a significant, albeit moderate (0.40 < r <0.55) correlation with disease activity (disease activity score in 28 joints-C reactive protein (DAS28-CRP)) [ 3 , 4 ]. In other studies, we evaluated the effects of therapies on global gene expression patterns in prospective synovial biopsy samples obtained prior to and 3 months after initiation of therapy with methotrexate, tocilizumab, rituximab or adalimumab.…”
Section: Introductionmentioning
confidence: 99%